2016
DOI: 10.1016/j.peptides.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive neuropeptides that stimulate spawning in the Sydney Rock Oyster (Saccostrea glomerata)

Abstract: The Sydney Rock Oyster, Saccostrea glomerata, is a socioeconomically important species in Australia, yet little is known about the molecular mechanism that regulates its reproduction. To address this gap, we have performed a combination of high throughput transcriptomic and peptidomic analysis, to identify genes and neuropeptides that are expressed in the key regulatory tissues of S. glomerata; the visceral ganglia and gonads. Neuropeptides are known to encompass a diverse class of peptide messengers that play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Global alignment shows high identity throughout the precursor and strict conservation of the mature peptide. RPCH was shown previously to be an ortholog of AKH in insects and APGWamide in mollusks96, where it has recently been shown to promote conditioning and spawning in oysters97. Early studies of crustacean RPCH suggested a function in pigmentation98, however later studies have proven that RPCH can regulate gonadal maturation in P. clarkii as determined by both in vitro and in vivo experiments99100.…”
Section: Discussionmentioning
confidence: 99%
“…Global alignment shows high identity throughout the precursor and strict conservation of the mature peptide. RPCH was shown previously to be an ortholog of AKH in insects and APGWamide in mollusks96, where it has recently been shown to promote conditioning and spawning in oysters97. Early studies of crustacean RPCH suggested a function in pigmentation98, however later studies have proven that RPCH can regulate gonadal maturation in P. clarkii as determined by both in vitro and in vivo experiments99100.…”
Section: Discussionmentioning
confidence: 99%
“…In cuttlefish, neuropeptides like APGWamide (Henry et al, 1997), FMRFamide (Henry et al, 1999) and sepiatocin (Henry et al, 2013) play a role in oocyte transport and capsular secretion. In other mollusks such as the Sydney Rock Oyster (Saccostrea glomerata), several neuropeptides induce egg laying in sexually mature individuals: egg-laying hormone (ELH), GnRH, APGWamide, buccalin, CCAPs (crustacean cardioactive peptides), and LFRFamide (In et al, 2016). In gastropods, ELH appears to be pivotal in egg-laying regulation, particularly in hermaphrodite snails such as Aplysia (Arch, 1972;Chiu et al, 1979;Chiu and Strumwasser, 1981) and Lymnaea (Ebberink et al, 1985;Geraerts et al, 1983;Vreugdenhil et al, 1985), whereas in gonochoric gastropods many neuropeptides also appear to be involved in addition to ELH.…”
Section: Introductionmentioning
confidence: 99%
“…From a structural point of view, analysis of the S. officinalis precursor predicted the release of 3 neuropeptides with very similar sequences, subsequently characterized by mass spectrometry (Zatylny-Gaudin et al, 2016). A special feature of these neuropeptides lies in the fact that although they are not amidated at their C-terminal end they keep the characteristic disulfide bond, in contrast to CCAPs from arthropods and bivalves (In et al, 2016). We named these neuropeptides based on the order of their occurrence in the precursor: SoCCAP1 (VFCNSFGGCTNI), SoCCAP2 (VFCNSYGGCKSF), and SoCCAP3 (VFCNSFGGCQN).…”
Section: Introductionmentioning
confidence: 99%
“…Genes encoding anti-oxidant enzymes were shown to be differentially expressed between disease-resistant and wild-type oysters, highlighting the potential for marker-assisted selection [ 22 ]. Molecular techniques have also yielded tools for the manipulation of broodstock condition, a development of critical importance for the hatchery production of selected animals [ 23 ]. Given that the black-lip and S .…”
Section: Introductionmentioning
confidence: 99%